Inertial Motion Capture Costume. (2017) - Szczęsna, Agnieszka; Pruszowski, Przemysław; Skurowski, Przemysław; Lach, Ewa; Słupik, Janusz; Pęszor, Damian; Paszkuta, Marcin; Polański, Andrzej; Wojciechowski, Konrad; Janiak, Mateusz; Lebek, Kamil
Abstract: The need to measure human motion and to estimate its kinematic and dynamic parameters in a real time appears in many fields such as medicine, sport, art and entertainment. This publication describes, inexpensive and easy to customize for many applications, Inertial Motion Capture Costume. The costume is based on IMU sensors and includes industry grade software that enables acquisition, visualization and analysis of human motion data.